Search-based endogenous asset liquidity and the macroeconomy - Wei Cui; Sören Radde (European Central Bank (ECB), 2016)
We endogenize asset liquidity in a dynamic general equilibrium model with search frictions on asset markets. In the model, asset liquidity is tantamount to the ease of issuance and resaleability of private financial claims, which is driven by investors' participation on the search market. Limited market liquidity of private claims creates a role for liquid assets, such as government bonds or at money, to ease financing constraints. We show that endogenising liquidity is essential to generate positive comovement between asset (re)saleability and asset prices. When the capacity of the asset market to channel funds to entrepreneurs deteriorates, investment falls while the hedging value of liquid assets increases, driving up liquidity premia. Our model, thus, demonstrates that shocks to the cost of financial intermediation can be an important source of flight-to-liquidity dynamics and macroeconomic fluctuations, matching key business cycle characteristics of the U.S. economy.
Keywords: E22; E44; G11; 330; asset search markets; endogenous asset liquidity; financial shocks; financing constraints; liquidity premium